ISOLATION, PATHOGENICITY TEST, CHARACTERIZATION AND IDENTIFICATION OF ENDOPHYTIC FUNGI OF SOYBEAN ( (L.) MERRIL) GLYCINE MAX (Journal of Plant Disease Sciences, 2024)
Endophytes are microbes that live in plant tissues without causing any damage to the host plants. Present study describes the isolation, pathogenicity test and identification of endophytic fungi from soybean. During this study, a total of 14 endophytic fungi isolated from soybean plant samples (leaves, stems and roots), i.e. five isolates from leaves, five isolates from stems and four isolates from roots were obtained. Amongst them, isolated from the leaves were Curvularia lunata, Cladosporium cladosporioides, Nigrospora sphaerica, Penicillium sp. and Paecilomyces lilacinus and isolated from stems were Alternaria alternata, Phomopsis sp. 1, Rhizoctonia sp., Phomopsis sp. 2 and Macrophomina phaseolina. Whereas, isolated from roots were Fusarium oxysporum, Aspergillus niger, Aspergillus sp. and Chaetomium sp. Fungi isolated as endophytes from Soybean (Glycine max (L.) Merril) Cv. JS-335 were tested in order to ascertain whether they are capable of causing disease symptoms in healthy soybean’s stem, root and leaves. The pathogenicity test of fourteen fungal endophytes was carried out by pin prick method (for stem endophytes), spore suspension method (for leaf endophytes), root or soil drenching method (for root endophytes). No any fungal species of endophytic fungi able to cause any diseased symptoms on soybean plant and remained healthy. Endophytic microorganisms have received considerable attention due to their biotechnological utility in several fields of agriculture, industry and medicine.
Keywords: Endophytes; Disease symptoms; Isolation; Soybean